Artifact Suppression in Imaging of Myocardial Infarction Using B(1)-Weighted Phased-Array Combined Phase-Sensitive Inversion Recovery - Kellman, Peter (2004)
Regions of the body with long T(1), such as cerebrospinal fluid (CSF), may create ghost artifacts on gadolinium-hyperenhanced images of myocardial infarction when inversion recovery (IR) sequences are used with a segmented acquisition. Oscillations in the transient approach to steady state for regions with long T(1) may cause ghosts, with the number of ghosts being equal to the number of segments. B(1)-weighted phased-array combining provides an inherent degree of ghost artifact suppression because the ghost artifact is weighted less than the desired signal intensity by the coil sensitivity profiles. Example images are shown that illustrate the suppression of CSF ghost artifacts by the use of B(1)-weighted phased-array combining of multiple receiver coils.